High Temperature Gallium Orthophosphate Transducers for NDT. (2016) - Kostan, M.; Mohimi, A.; Nageswaran, C.; Dhutti, A.; Gan, T.-H.; Wrobel, L.; Selcuk, C.
Abstract: A transducer has been manufactured leading towards development of an ultrasonic system to operate up to 580°C for non-destructive testing (NDT) and monitoring in power plants. The manufactured transducer has a simple design based on the piezoelectric single crystal gallium orthophosphate (GaPO4 ) which allows ultrasonic measurements to be performed up to considerably high temperature (HT) levels required in this study. Usually a critical aspect when performing HT ultrasonic NDT– acoustic coupling to the test-material, has been resolved using a commercially available HT silver adhesive which provides permanent installation of the transducer on the structure to be tested. This also means that for future application in an industrial environment drilling and/or machining intervention requirements will be reduced significantly. Finally, the GaPO4 transducer's sensitivity ( f= 3.5 MHz) has been successfully tested through measurements on a steel block containing an artificial defect with known geometry (side-drilled hole (SDH) with d= 0.8 mm) up to the target temperature of 580°C keeping the defect's signal-to-noise ratio (SNR) above 6 dB which is high enough for NDT practice.